The A Key Issue in Bharati Mukherjee’s Novels: Case study of Cultural Shock - Amit Dhawan , Dinesh Kumar Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Bharati Mukherjee is a Third World Feminist essayist whose main focus is on issues and concerns concerning South Asian women, particularly in India; yet, she claims that her views are more comparable to those of North American women. She differs from other authors in the way she handles her champions (Indian ladies outsiders), most notably with their social stun, which evicts them from life, either directly or indirectly. Tara Banerjee in 'The Tiger's Daughter,' Dimple in 'Spouse,' Jyoti in 'Jasmine,' Devi in 'Abandon it to me,' three sisters - Padma, Parvathi, and Tara in 'Alluring Daughters,' and Tara in 'The Tree Bride,' all demonstrate this. Despite the fact that the courageous women are portrayed as strong and assertive, they are nonetheless subjected to the 'culture stun' behaviour. They have a strong potential for adaptability; they are well-positioned to modify their lives for the better, if necessary, as well as to acknowledge the painful truths of their life in any event. This study aims to capture the core cause, the central notion that underpins the dilemma that so many fans of her works are experiencin